2016
DOI: 10.1111/ibi.12431
|View full text |Cite
|
Sign up to set email alerts
|

Size and material of model parasitic eggs affect the rejection response of Western Bonelli's Warbler Phylloscopus bonelli

Abstract: Given the high costs of brood parasitism, avian hosts have adopted different defences to counteract parasites by ejecting the foreign egg or by deserting the parasitized nest. These responses depend mainly on the relative size of the host compared with the parasitic egg. Small hosts must deal with an egg considerably larger than their own, so nest desertion becomes the only possible method of egg rejection in these cases. The use of artificial model eggs made of hard material in egg-recognition experiments has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…In this study, Oriental Reed Warblers, as one of the most common hosts of cuckoos, have a nearly 100% rejection rate for non-mimetic eggs, similar to the population in northeastern China, which rejected both blue (n = 15) and white (n = 24) model eggs at a rate of 100% (Wang et al 2021) and the Japanese population (94%, n = 33; Lotem et al 1995), suggesting that the Oriental Reed Warbler possesses an extremely strong egg recognition ability. However, egg rejection of another population of Oriental Reed Warblers (Li et al 2016(Li et al , 2020 was slightly lower than that of this population, possibly because the material and size of experimental eggs used may influence on the host's completion of egg rejection (Roncalli et al 2017;Li et al 2020).…”
Section: Discussionmentioning
confidence: 65%
“…In this study, Oriental Reed Warblers, as one of the most common hosts of cuckoos, have a nearly 100% rejection rate for non-mimetic eggs, similar to the population in northeastern China, which rejected both blue (n = 15) and white (n = 24) model eggs at a rate of 100% (Wang et al 2021) and the Japanese population (94%, n = 33; Lotem et al 1995), suggesting that the Oriental Reed Warbler possesses an extremely strong egg recognition ability. However, egg rejection of another population of Oriental Reed Warblers (Li et al 2016(Li et al , 2020 was slightly lower than that of this population, possibly because the material and size of experimental eggs used may influence on the host's completion of egg rejection (Roncalli et al 2017;Li et al 2020).…”
Section: Discussionmentioning
confidence: 65%
“…Additionally, hosts may accept a parasitic egg sometimes, even if it has been recognized (i.e., evidence of egg‐pecking behavior from video sampling) (Guigueno & Sealy, 2012; Soler, Fernández‐Morante, Espinosa, & Martín‐Vivaldi, 2012). This phenomenon has been recorded in several small‐bodied hosts (about 10 g; Roncalli et al., 2017), especially in experiments using artificial model eggs made from a hard material (Martín‐Vivaldi, Soler, & Møller, 2002; Šulc et al., 2016). However, this effect is thought to be less constrained in large or medium‐sized hosts that grasp or puncture foreign eggs in their nests (Soler, Ruiz‐Raya, Roncalli, & Ibáñez‐Álamo, 2017).…”
Section: Introductionmentioning
confidence: 78%
“…A large number of studies have confirmed that hosts use cues from egg coloration or maculation mimicry to reject eggs (Honza & Cherry, 2017; Šulc, Procházka, Capek, & Honza, 2016), but evidence for using egg coloration as an egg rejection cue is rare (Šulc et al., 2019). Egg size can significantly affect the mode of egg rejection by forcing hosts to desert nests instead of ejecting eggs if they are constricted by their limited bill size or the weight of a heavy parasitic egg (Stokke et al., 2010; Roncalli, Ibáñez‐Álamo, & Soler, 2017; but see Soler, Ruiz‐Raya, Roncalli, & Ibáñez‐Álamo, 2015). Additionally, hosts may accept a parasitic egg sometimes, even if it has been recognized (i.e., evidence of egg‐pecking behavior from video sampling) (Guigueno & Sealy, 2012; Soler, Fernández‐Morante, Espinosa, & Martín‐Vivaldi, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This conclusion is still important from a methodological point of view, because various materials are used to manufacture the artificial egg models. However, what is still missing from the experimental repertoire is a model egg stimulus that can be pierced by hosts whose beaks are too small for grasp rejection (e.g., Roncalli et al, 2017). Finally, we compared the eggshell traits' impact on egg rejection by hosts parasitized by Old World cuckoos vs. cowbirds and, contrary to expectations, found no statistical differences between these diverse set of hosts (Figure 4).…”
Section: Discussionmentioning
confidence: 86%